Super-resolution fight club: assessment of 2D and 3D single-molecule localization microscopy software - Sage, Daniel; Pham, Thanh-An; Babcock, Hazen; Lukes, Tomas; Pengo, Thomas; Chao, Jerry; Velmurugan, Ramraj; Herbert, Alex; Agrawal, Anurag; Colabrese, Silvia; Wheeler, Ann; Archetti, Anna; et al. (Nature methods, 2019)
With the widespread uptake of two-dimensional (2D) and three-dimensional (3D) single-molecule localization microscopy (SMLM), a large set of different data analysis packages have been developed to generate super-resolution images. In a large community effort, we designed a competition to extensively characterize and rank the performance of 2D and 3D SMLM software packages. We generated realistic simulated datasets for popular imaging modalities-2D, astigmatic 3D, biplane 3D and double-helix 3D-and evaluated 36 participant packages against these data. This provides the first broad assessment of 3D SMLM software and provides a holistic view of how the latest 2D and 3D SMLM packages perform in realistic conditions. This resource allows researchers to identify optimal analytical software for their experiments, allows 3D SMLM software developers to benchmark new software against the current state of the art, and provides insight into the current limits of the field.
Keywords: Imaging, Three-Dimensional; Image Processing, Computer-Assisted; algoritmy; software; Algorithms; Single Molecule Imaging; zobrazení jednotlivé molekuly; zobrazování trojrozměrné; Software; počítačové zpracování obrazu